Carnatic approaches (to) experimental music: practice-based interventions from the borders - Krishnamurthy, Nakul (The University of Edinburgh, 2024)
Borders, be they musical, cultural, ideological, or disciplinary, can be endlessly challenging but bountifully fertile. They are spaces created and traversed by overlapping and disjunctive territorial knowledges, ways of thinking, and modes of being where the imposing weight of cultures, traditions, and artistic forms can be negotiated. At the same time, they are spaces from which new thoughts and strategies can emerge—ones that hold the potential to challenge and dismantle the hegemonic orders that they develop contiguously with. This research positions my music practice in and as a border location from which new knowledges emerge to question the Brahmanical hierarchical order in south Indian performing artforms and global Western hegemonic orders in an effort to challenge their modern/colonial epistemologies. By modern/colonial epistemologies, I mean the ‘universal’ rational scientific epistemological models erected by the Western colonial order, as well as its legacies and redeployments in anticolonial models at the postcolonial Indian locus of enunciation that continue to propagate its marginalising and Orientalising tendencies. Practice becomes the site at which these rational scientific models and its Orientalist legacies and tendencies are contested, and new embodied ways of thinking are posited as challenges. The research includes a portfolio of music-based works where Carnatic music is alternatively imagined at its intersections with electronic, experimental, Hindustani, Western Classical, and Indian popular musics. These works performatively present embodied ways of thinking and being along and across aesthetic and cultural borders to develop performative critiques of modern/colonial epistemologies and devise de-Brahmanical and decolonial strategies. The works, as sites of agency and active aesthetic and political interventions, reveal a border locus of enunciation that resources embodied experiential, performative, trans-cultural artistic and aesthetic knowledges to subvert regional and global hegemonic structures. The accompanying thesis explicates the knowledges performatively presented in the portfolio of works. It adopts postcolonial and decolonial lenses to examine the political propositions performatively presented and develops these knowledges further by engaging with broader academic discourses in the theoretical domain. Using tools of ‘border thinking’ (Mignolo 2012 [2000]) and ‘double critique’ (Khatibi 2019 [1983]), the thesis speaks from a border location along the boundaries of both Western and Brahmanical hegemonic orders and proposes new theoretical tools based on notions of embodiment and disembodiment that can intervene and dislodge the supremacy of modern/colonial worldview. The thesis therefore works in tandem with the portfolio, both resourcing and renewing each other, to propose embodied decolonial knowledges that advance alternative modalities of thinking marginalised by the Brahmanical and Western modes of thought.
Keywords: creative music practice; Carnatic music; Indian Classical music; intersections of musical genres; trans-cultural art; trans-cultural aesthetic; border thinking